2020
DOI: 10.1111/ijcp.13831
|View full text |Cite
|
Sign up to set email alerts
|

Combination of prealbumin and tuberculosis‐specific antigen/phytohemagglutinin ratio for discriminating active tuberculosis from latent tuberculosis infection

Abstract: Background Given that there is no rapid and effective method for distinguishing active tuberculosis (ATB) from latent tuberculosis infection (LTBI), the discrimination between these two statuses remains challenging. This study sought to investigate the value of nutritional indexes and tuberculosis‐specific antigen/phytohemagglutinin ratio (TBAg/PHA ratio) for distinguishing ATB from LTBI. Methods Participants were consecutively recruited based on positive T‐SPOT.TB results between January 2018 and January 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Furthermore, we found that lymphocyte non-specific function detection including CD4 + T cell non-specific function, CD8 + T cell nonspecific function, and NK cell non-specific function could be used to distinguish between ATB and LTBI. In view of the fact that the combination of multiple parameters may perform better than single parameter alone in many studies (20,21,40), we further successfully established a three-index diagnostic model that could discriminate ATB from LTBI with good utility based on the combination of lymphocyte non-specific function and T-SPOT assay. The diagnostic model based on the combination of CD4 + T cell non-specific function, NK cell non-specific function, and CFP-10 spot number established in the present study was 90.63% specific and identified 83.67% of ATB cases, indicating that it could be used as a rule-in ATB diagnostic test to allow rapid treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that lymphocyte non-specific function detection including CD4 + T cell non-specific function, CD8 + T cell nonspecific function, and NK cell non-specific function could be used to distinguish between ATB and LTBI. In view of the fact that the combination of multiple parameters may perform better than single parameter alone in many studies (20,21,40), we further successfully established a three-index diagnostic model that could discriminate ATB from LTBI with good utility based on the combination of lymphocyte non-specific function and T-SPOT assay. The diagnostic model based on the combination of CD4 + T cell non-specific function, NK cell non-specific function, and CFP-10 spot number established in the present study was 90.63% specific and identified 83.67% of ATB cases, indicating that it could be used as a rule-in ATB diagnostic test to allow rapid treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that poor immune status was one characteristic of ATB patients, suggesting that the evaluation of host immunity could be applied as a potential direction for TB diagnosis and monitoring (13,(20)(21)(22). Unfortunately, difficulties existed in host immunity evaluation of ATB patients due to the limitations of current tests such as lymphocyte subset analysis and the measurement of serum protein (23).…”
Section: Introductionmentioning
confidence: 99%
“…TB is generally considered to be a disease with malnutrition. Some previous studies have reported the low level of serum iron ( 55 ) and prealbumin ( 56 ) in ATB patients. Thus, the low level of lymphocyte number and function found in our research echoed these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, immunodiagnostics has received considerable attention as an alternative for discrimination of MTB infection status in recent years (63)(64)(65)(66)(67)(68)(69)(70). Nevertheless, the identified biomarkers including proteins and cytokines in serum or plasma for diagnostic aim may not be specific for TB due to the influence brought by other immune related diseases such as infection and autoimmune diseases (71)(72)(73)(74)(75)(76)(77). Thus, an intensified search for suitable host-specific biomarkers targeting TB diagnostic purpose was urgently needed (78).…”
Section: Discussionmentioning
confidence: 99%